Iron (II) phthalocyanine loaded tourmaline efficiently activates PMS to degrade pharmaceutical contaminants under solar light - Wang, Zhendong (Environmental technology, 2023)
Iron (II) phthalocyanine (FePc) is loaded on the surface of the tourmaline (TM) by the reflow method to obtain FePc/TM. This research effectively prevents the π-π stacking of FePc, increased the effective utilization rate of PMS activation under solar light, and further improved the catalytic performance of the catalytic system. The catalytic oxidation efficiency of FePc/TM on carbamazepine (CBZ) and sulfadiazine (SD) can reach 99% under solar light for 15 and 5 min, the total organic carbon (TOC) removal rate can reach 58% and 69% under solar light for 120 min. After 6 cycles, the CBZ removal rate remained above 95%. In addition, the FePc/TM catalytic system has an excellent removal rate for other pharmaceuticals. The results of spin-trapped electron paramagnetic resonance and classical quenching experiments show that FePc/TM can effectively activate PMS to generate active species under solar light, including superoxide radical (•O2-), singlet oxygen (1O2), hydroxyl radicals(•OH), and sulphate radicals (SO4•-). The intermediates of CBZ were identified by Ultra-high performance liquid chromatography and high resolution mass spectrometry, and the degradation pathway was proposed. As the reaction progresses, all CBZ and intermediates are reduced and converted into small acids, or mineralized to H2O, CO2. This work provides an alternative method for the design of efficient activation of PMS activation catalysts under solar light to eliminate residual pharmaceuticals in actual water bodies